1987
DOI: 10.1126/science.2884727
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of Information Storage in the Nervous System

Abstract: The use of molecular biological approaches has defined new mechanisms that store information in the mammalian nervous system. Environmental stimuli alter steady-state levels of messenger RNA species encoding neurotransmitters, thereby altering synaptic, neuronal, and network function over time. External or internal stimuli alter impulse activity, which alters membrane depolarization and selectively changes the expression of specific transmitter genes. These processes occur in diverse peripheral and central neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(47 citation statements)
references
References 41 publications
0
44
0
3
Order By: Relevance
“…4). Induction of the TH gene by PKA might thus be an important mediator of alterations of neuronal activity in response to environmental stimuli (7). Additionally, PKA can exert important acute regulation of TH activity in response to many stimuli by phosphorylation of the enzyme molecule (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Induction of the TH gene by PKA might thus be an important mediator of alterations of neuronal activity in response to environmental stimuli (7). Additionally, PKA can exert important acute regulation of TH activity in response to many stimuli by phosphorylation of the enzyme molecule (3).…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3; for review see ref. 4) or delayed increases in TH (5)(6)(7). The latter responses correlate with increases in TH mRNA and enzyme molecules and are blocked by inhibitors of RNA and protein synthesis, indicating that transcriptional regulation of the TH gene is directly involved (8,9).…”
mentioning
confidence: 99%
“…Depolarization, which leads to a rapid fourfold increase in VGF mRNA levels, triggers calcium influx through voltage-gated calcium channels. Genes regulated by depolarization include the immediate-early genes (9,37,75,76,82,107) and those encoding neuropeptide and neurotransmitter biosynthetic enzymes (12,31,50,103). Since VGF polypeptide is secreted through a regulated pathway in PC12 cells and its release is stimulated by depolarization (80), the elevation in VGF mRNA levels that was observed after depolarization may be a response to depletion of cellular VGF stores, much as the pituitary genes that encode growth hormone, pro-opiomelanocortin, and prolactin respond to stimulated secretion of the respective peptide hormones by increasing the rate of gene transcription (7,8,30,34,78).…”
Section: Discussionmentioning
confidence: 99%
“…Graybiel and Ragsdale (38) have found that butyryl-and acetylcholinesterase levels are also higher in regions of visual cortex deprived of input by unilateral enucleation. In culture systems as well, reductions in electrical activity may increase the expression of some neurotransmitter systems (39).…”
Section: Discussionmentioning
confidence: 99%